2018
DOI: 10.1021/acsbiomaterials.7b00962
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Mineralization Using Chondrocyte Membrane Nanofragments

Abstract: Biomineralization involves complex processes and interactions between organic and inorganic matters, which are controlled in part by the cells. The objectives of this study were, first, to perform a systematic and ultrastructural investigation of the initial mineral formation during secondary ossification center of mouse femur based on material science and biology viewpoint, and then develop novel biomaterials for mineralization based on the in vivo findings. First, we identified the very initial mineral depos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
76
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 29 publications
(78 citation statements)
references
References 33 publications
2
76
0
Order By: Relevance
“…A possible mechanism could be associated with early phosphatase activity (data not shown), which is known to be fundamental for bone mineralization . Collectively, these data is in accordance with a previous article showing that nanofragments from cell membrane can also be nucleation site for mineral formation . Therefore, nanofragmentation of cell and MV structures can be an important tool for enhancing mineralization toward in vitro bone tissue synthesis.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…A possible mechanism could be associated with early phosphatase activity (data not shown), which is known to be fundamental for bone mineralization . Collectively, these data is in accordance with a previous article showing that nanofragments from cell membrane can also be nucleation site for mineral formation . Therefore, nanofragmentation of cell and MV structures can be an important tool for enhancing mineralization toward in vitro bone tissue synthesis.…”
Section: Discussionsupporting
confidence: 88%
“…25 Additionally, in our previous article, we have demonstrated that amorphous calcium phosphate minerals can be preserved even after preparation of thin TEM film samples, as confirmed by elemental mapping and electron diffraction. 3 Therefore, the results of this study indicate that an amorphous mineral phase is initially formed inside the MVs, which then crystallize into hydroxyapatite.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations